Lignin provides mechanical support to herbaceous peony (Paeonia lactiflora Pall.) stems - Zhao, Daqiu (Hortic Res, 2020)
Stem bending caused by mechanical failure is a major constraint for high-quality herbaceous peony (Paeonia lactiflora Pall.) cut flowers, but little is known about the underlying factors. In this study, two P. lactiflora cultivars, Xixia Yingxue (bending) and Hong Feng (upright), were used to investigate differences in stem bending. The results showed that the stem mechanical strength of Hong Feng was significantly higher than that of Xixia Yingxue, and the thickening of the secondary cell wall and the number of thickened secondary cell wall layers in Hong Feng were significantly higher than those in Xixia Yingxue. Moreover, compared with Xixia Yingxue, Hong Feng showed greater lignification of the cell wall and lignin deposition in the cell walls of the sclerenchyma, vascular bundle sheath and duct. All three types of lignin monomers were detected. The S-lignin, G-lignin, and total lignin contents and the activities of several lignin biosynthesis-related enzymes were higher in Hong Feng than in the other cultivar, and the S-lignin content was closely correlated with stem mechanical strength. In addition, 113,974 full-length isoforms with an average read length of 2106 bp were obtained from the full-length transcriptome of P. lactiflora stems, and differential expression analysis was performed based on the comparative transcriptomes of these two cultivars. Ten lignin biosynthesis-related genes, including 26 members that were closely associated with lignin content, were identified, and multiple upregulated and downregulated transcription factors were found to positively or negatively regulate lignin biosynthesis. Consequently, lignin was shown to provide mechanical support to P. lactiflora stems, providing useful information for understanding the formation of P. lactiflora stem strength.